A Study on the Frequency of MRSA Colonization among Attendants of Burn Patients and Its Association with Subsequent MRSA Isolation from Their Infected Burn Wounds at a Tertiary Care Burn Center - Zubeda Irshad, Munir Hussain, Tehmina Jalil, Rabbia Mahboob, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hospitalized patients with burns are particularly vulnerable to healthcare-associated infections, especially those caused by methicillin-resistant Staphylococcus aureus (MRSA). While attention has largely focused on transmission within the healthcare setting, the potential role of visitors and close caregivers in introducing MRSA remains underexplored. This study aimed to determine the frequency of MRSA colonization among the attendants of burn patients and assess its association with subsequent MRSA isolation from suspected burn wound infections. Methods: A cross-sectional study was conducted over six months at the Burns and Plastic Surgery Centre in Hayatabad, Peshawar. A total of 260 participants were enrolled, comprising 130 burn patients and 130 of their primary attendants. Nasal swabs from attendants and wound swabs from patients were processed for MRSA using standard microbiological techniques. Data were analyzed using SPSS version 25.0, with statistical significance set at p < 0.05. Results: MRSA colonization was identified in 16.6% of attendants. Among patients, 34.6% had MRSA-positive wound cultures. A statistically significant association was found between MRSA-positive attendants and patient infections (p = 0.034), with 63.6% of patients whose attendants were colonized developing MRSA wound infections. Conclusion: The findings indicate that MRSA colonization among attendants may contribute to transmission of infection in burn units. Although the association was not highly significant, the elevated risk highlights the need for enhanced infection control strategies. Screening and hygiene education for attendants in high-risk units may serve as a preventive measure to reduce nosocomial MRSA transmission. Keywords: MRSA, burn patients, attendants, nosocomial infection, colonization, wound infection, hospital-acquired infection, infection control